Artifact‐Free Quantification and Sequencing of Rare Recombinant Viruses by Using Drop‐Based Microfluidics. Issue 15 (7th September 2015) - Tao, Ye; Rotem, Assaf; Zhang, Huidan; Cockrell, Shelley K.; Koehler, Stephan A.; Chang, Connie B.; Ung, Lloyd W.; Cantalupo, Paul G.; Ren, Yukun; Lin, Jeffrey S.; Feldman, Andrew B.; Wobus, Christiane E.; et al.
Abstract Recombination is an important driver in the evolution of viruses and thus is key to understanding viral epidemics and improving strategies to prevent future outbreaks. Characterization of rare recombinant subpopulations remains technically challenging because of artifacts such as artificial recombinants, known as chimeras, and amplification bias. To overcome this, we have developed a high‐throughput microfluidic technique with a second verification step in order to amplify and sequence single recombinant viruses with high fidelity in picoliter drops. We obtained the first artifact‐free estimate of in vitro recombination rate between murine norovirus strains MNV‐1 and WU20 co‐infecting a cell (Prec=3.3×10−4±2×10−5) for a 1205 nt region. Our approach represents a time‐ and cost‐effective improvement over current methods, and can be adapted for genomic studies requiring artifact‐ and bias‐free selective amplification, such as microbial pathogens, or rare cancer cells.